Fluxo de pólen heteroespecífico entre espécies sincronopátricasde Psychotria L. (Rubiaceae) - Borges, João Paulo Raimundo (2017)
Several species of Psychotria L. are common in the understore of semideciduous forests of the Center-West region of Brazil. Often these species occur in sympatry and present overlap in their flowering periods. Recent studies have revealed the occurrence of pollinators sharing among synchronopatric species within the genus Psychotria, with a variation in this sharing according to the interacting species. In the present study, it was investigated whether the exchange of heterospecific pollen occurs between sympatric species and what the intensity of this flow is in comparison with the intraspecific flow. The floral synchrony and nectar production among these sympatric species of Psychotria were also verified to confirm the possibility of interspecific pollen exchange in this system. The data collection took place during the months of November and December of 2015, in a semidecidual forest in the Municipal Park Setor Santa Cruz, municipality of Catalão, GO. The collected data were: floral phenology, nectar production, reciprocity between anthers and stigma, and rate of fluorescent powder flow between species and their floral morphotypes. Our data showed that the flowering peaks were synchronous among Psychotria species, with a significant difference in the nectar production between the species, being larger and renewable after the first removal for P. nitidula, but with higher sugar concentration in P. prunifolia. In relation to reciprocity intraspecific and interspecific, there was no deviation from that expected for distal species, with the reciprocity being greater between the reproductive organs of the same species than between the reproductive organs of different species. Comparing the fluorescent powder flow, it was observed that P. prunifolia presented a higher rate of exclusive visits, while P. nitidula presented more illegitimate visits, mainly for its thrum morph, which promoted greater donation of heterospecific fluorescent powder. P. hoffmannseggiana presented low intensity of donation and reception of fluorescent powder, being all of them interspecific. Therefore, there was a greater illegitimate fluorescent powder flow among the study species than legitimate.